The Authority of Malim Kampung and Hatobangon in Addressing Household Conflicts in Tanjung Mompang Village Community, Panyabungan Utara District, Mandailing Natal - Efendi, Rahmad (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2020)
This study aims to determine the position of the village malim and Hatobangon as rights in divorcing husband and wife who are at odds with the village community of Tanjung Mompang as well as the factors behind this authority in terms of Islamic law. This research is a field research (field research) with a social approach (social opprouch). The results of this study indicate that the understanding and practice of the Tanjung Mompang community regarding the authority of the village of Malim and Hatobangon as rights is motivated by various reasons, including community adherence to traditions and customs that they have adopted from generation to generation, geographical factors in the village of Tanjung Mompang which are located in the interior and in The mountains cause the development of law to lag, especially in the issue of divorce, the social conditions of society which are closed and do not mingle with other communities and the lack of socialization and guidance carried out by the government towards the community of Tanjung Mompang village. Geographical and sociological conditions such as this make the position of the village malim and Hatobangon as hakam so high and their decisions are obeyed and respected, so that the village malim and hatobangon who act as hakam hakam have the authority to decide the divorce between the disputing husband and wife. In Islamic law, hakam can only reconcile and find a solution that can stop disputes. Both rights must not order the husband and wife to divorce. In other words, the two rights do not have the authority to separate the husband and wife if the husband who is disputing is not asked. Although the people of Tanjung Mompang are a society that adheres to the Sayafi'i mazhab, in terms of the authority of a hakam in deciding a divorce for a husband and wife who is in dispute, it is not in line with the Syafi'i mazhab.